2020
DOI: 10.3390/ijerph17249264
|View full text |Cite
|
Sign up to set email alerts
|

Parental Hesitancy and Concerns around Accessing Paediatric Unscheduled Healthcare during COVID-19: A Cross-Sectional Survey

Abstract: A decrease in attendance at emergency departments among paediatric populations has been reported during the Coronavirus Disease 2019 (COVID-19) pandemic. The present study sought to understand parents’ hesitancy and concerns around accessing healthcare during the pandemic using a cross-sectional survey of parents of children under the age of 16 (N = 1044) in Ireland. Multinomial and logistic regression analyses were used to determine the factors that influenced avoidance and hesitancy. In total, 34% of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
5
48
0
5
Order By: Relevance
“…The cases of delayed presentations outlined by clinicians supports the findings of previous studies [5,7,8] and this study provides further insight into this phenomenon, highlighting the impact of parental hesitancy to attend the ED due to COVID-19 [9]. Public health messaging clearly impacted parents faced with making decisions around seeking care for children, thus clear and uncomplicated communication is essential [9]. The positive reaction to infection control measures displayed by parents suggests that a public communication strategy, clearly outlining the measures in place at the ED, can help to combat fears and reassure parents to continue to present [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The cases of delayed presentations outlined by clinicians supports the findings of previous studies [5,7,8] and this study provides further insight into this phenomenon, highlighting the impact of parental hesitancy to attend the ED due to COVID-19 [9]. Public health messaging clearly impacted parents faced with making decisions around seeking care for children, thus clear and uncomplicated communication is essential [9]. The positive reaction to infection control measures displayed by parents suggests that a public communication strategy, clearly outlining the measures in place at the ED, can help to combat fears and reassure parents to continue to present [7].…”
Section: Discussionsupporting
confidence: 85%
“…Lower attendance rates have been attributed to reduced infectious diseases and injuries due to public health measures implemented. Furthermore, parental hesitancy to attend hospitals due to fear of COVID-19 and a misinterpretation of public health messaging may have also contributed to reduced presentations [9].…”
Section: Introductionmentioning
confidence: 99%
“…Parental anxieties surrounding hospital attendance during the pandemic are documented, [24] which could contribute to reduced attendances/admissions. However, a UK-based prospective study found only 3.8% of ED presentations during were delayed due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians explained that parents were unaware of the infection control measures put in place in hospitals, such as streaming and triaging for COVID-19, and reacted positively and felt reassured when observing the measures implemented: "I think most of them were very reassured when they came in because they were told no, we had a separate COVID streaming area." [9] 2.2 Stay Home, Stay Safe: Public Health Messaging As cases of COVID-19 rst began to increase in Ireland, authorities introduced restrictions on movement and issued public health advice, instructing people to stay at home. The initial drop in ED attendances coincided with this messaging and a number of clinicians felt it may have led some parents to believe they should not attend hospitals, particularly for issues that parents perceived to be not absolutely urgent:…”
Section: Fear Of Covid-19mentioning
confidence: 99%
“…Lower attendance rates have been attributed to reduced infectious diseases and injuries due to public health measures implemented. Furthermore, parental hesitancy to attend hospitals due to fear of COVID-19 and a misinterpretation of public health messaging (9).…”
Section: Introductionmentioning
confidence: 99%